DESAIN DIDAKTIS KONSEP PECAHAN UNTUK KELAS III SEKOLAH DASAR - Romdhani, Wina; Suryadi, Didi (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2016)
Abstract: This research is motivated learning phenomenon obstacle concept of fractions in fourth grade student. Research using DDR design. The purpose of this study to explore the learning obstacle, designing didactic design, implement and analyze the process and results of the implementation design. Data was collected by documentation, interviews, tests and observation. The research findings reveal the five types of barriers to learning students on the concept of fractions. Didactic design that was developed consisting of 4 lesson design and implement learning in third grade elementary school. The implementation results show the tendency of students in a particular response. Most students can achieve learning objectives are set, which means this didactic design can accommodate students' learning trajectory.Keywords: Learning Obstacle, didactic design, concept of fractions, didactical Design ResearchAbstrak: Penelitian ini dilatarbelakangi fenomena learning obstacle konsep pecahan pada siswa kelas IV SD. Penelitian menggunakan desain DDR. Tujuan penelitian ini untuk mengeksplorasi learning obstacle, merancang desain didaktis, mengimplementasikannya dan menganalisis proses dan hasil implementasi desain. Pengumpulan data dilakukan dengan dokumentasi, wawancara, tes dan observasi. Temuan penelitian mengungkap lima tipe hambatan belajar siswa pada konsep pecahan. Desain didaktis yang dikembangkan terdiri dari 4 lesson design dan diimplementasikan pada pembelajaran di kelas III SD. Hasil implementasi menunjukkan terdapat kecenderungan siswa pada respon tertentu. Sebagian besar siswa dapat mencapai tujuan pembelajaran yang ditetapkan yang berarti desain didaktis ini dapat mengakomodasi learning trajectory siswa.Kata Kunci: Learning Obstacle, Desain didaktis, Konsep pecahan, Didactical Design Research